An isolate of Apple stem grooving virus associated with Cleopatra mandarin fruit intumescence - Lovisolo,Osvaldo (2003)
A citrus tatter leaf isolate (CTLV-Cl) of Apple stem grooving virus (ASGV) has been found to be associated with a fruit rind intumescence in Cleopatra mandarin (Citrus reshni) in Limeira (SP). The CTLV-Cl was mechanically transmitted to the main experimental herbaceous hosts of CTLV. Chenopodium quinoa and C. amaranticolor reacted with local lesions and systemic symptoms while other test plants reacted somewhat differently than what is reported for CTLV. A pair of primers designed for specific detection of ASGV and CTLV amplified the expected 801 bp fragment from the CTLV-Cl-infected plants. Typical capillovirus-like particles were observed by the electron microscope in experimentally infected C. quinoa and C. amaranticolor leaves.